Improvement the properties of attention in the conditions of NUS (Actual Problems of Psychology in Educational Institutions, 2021)
Results of an experiment to study the attention of students ofthe third level of education in NUS are presented in the article. Theoreticalgains of attention as a form of mental activity of man, which is manifestedin the direction and concentration of consciousness on certain objects, wereanalyzed. Ascertaining and formative stages of research were described. Itwas determined how such features of attention as concentration, switching,fluctuation and volume have changed. It was determined how such featuresof attention as concentration, switching, fluctuation and volume changed.Types and methods of work to improve the properties of attention weredescribed. Results of an experiment the properties of attention wereanalyzed.The conclusion was done that work on improving concentration,switching, distribution of attention would be effective in the case ofsystematic work.
Keywords: attention, concentration research, observation